Hydroclimatic conditions and sediment provenance in the northeastern Arabian Sea since the late Miocene: insights from geochemical and environmental magnetic records at IODP Site U1457 of the Laxmi Basin. (10th April 2023) - Alam, Mahboob; Muguli, Tripti; Gurumurthy, G.P.; Arif, Mohammad; Sohrin, Yoshiki; Singh, Arun Deo; Radhakrishna, T.; Pandey, Dhananjai Kumar; Verma, Komal
Abstract: Palaeo-monsoon and palaeoclimate conditions over Southeast Asia are a matter of debate despite notable studies on the continental and oceanic sedimentary record. The present study investigates the environmental magnetic and geochemical records preserved in the deep marine sediments of the northeastern (NE) Arabian Sea to elucidate the erosion history of the western Himalayas and its link with the prevailing hydroclimatic conditions since the late Miocene. For this, the sediment core retrieved during International Ocean Discovery Program (IODP) Expedition 355 at Site U1457 in the NE Arabian Sea has been explored. The results reveal that the hydroclimatic conditions were predominantly arid during the late Miocene, except for humid intervals from 6.1 Ma to 5.6 Ma. Humid climate conditions in the Indus River Basin returned during the mid-Pliocene and continued to the Pleistocene with an intense chemical weathering regime from 1.9 Ma to 1.2 Ma. The dominant sediment source to the NE Arabian Sea at Site U1457 during the late Miocene and the Pliocene was the Indus River, while during the Pleistocene, mixed sediments brought by the Indus River and the Peninsular Indian rivers were observed. The sediment contribution from a chemically less altered mafic source (the Deccan basalts) increased between 1.2 Ma and 0.2 Ma, possibly linked to a weak Indian Summer Monsoon. The summer monsoon wind strength and associated shift in the Inter-Tropical Convergence Zone (ITCZ) influenced the dominant sediment provenance at Site U1457 of the Laxmi Basin.